Dynamic thermal performance prediction model for the flat-plate solar collectors based on the two-node lumped heat capacitance method. (October 2016) - Deng, Jie; Ma, Rongjiang; Yuan, Guofeng; Chang, Chun; Yang, Xudong
Highlights: Presented the collector dynamic prediction model based on two-node lumped heat capacitance. Identified the solar collector dynamic response time constant. Relation between the dynamic and static time constants was interpreted. The correlation between the amended model and the TICM was elaborated. The proposed dynamic prediction model was validated by experimental tests. Abstract: Two-node lumped heat capacitance model of the flat-plate solar collectors is derived strictly based on the concept of the collector flow efficiency factor F ′ . It is found that the obtained first-order differential model turns out to be the amended quasi-dynamic test (QDT) model. The collector dynamic response time constant τ d is identified referring to the first-order response system in automatic control theory. Then the dynamic thermal performance prediction model for the flat-plate solar collectors on the basis of the amended QDT model is deduced using integral treatment within a small time interval in order to extend the thermal inertia correction model (TICM) to be fit for different conditions, such as moderate or intensive change rates of the collector inlet temperature, wide-range ratios of the diffuse radiation to global radiation, different incidence angles, etc. Correlation between the presented prediction model and the TICM base on the steady-state test (SST) for the flat-plate solar collectors is elucidated and the relation between the collector dynamic response time constant τ d and the static time constant τ C is elaborated. Finally, experimental tests of both the steady-state tests and dynamic tests with a specific flat-plate solar air collector are conducted to verify the performance of the proposed dynamic prediction model and corresponding parameters. It is verified that the presented prediction model in terms of the collector dynamic response time constant τ d can accurately predict the dynamic thermal performances of the flat-plate solar air collector under different conditions.